PARAMETER MODIFICATION OF THE ?CDM COSMOLOGY MODEL AS SOLUTIONS FOR DIFFERENCES IN MEASUREMENT OF H0 VALUES - Hasan Khatami, Akbar
The Hubble constant (H0), which represents the current rate of expansion of the universe, is one of the most important parameters in cosmology and is necessary for the determination of other cosmological quantities including the age of the universe. The Hubble constant was rst introduced by Edwin Hubble in 1929, as the gradient of the relation between redshift and extragalactic distance. Now the measurement of the H0 value is becoming more accurate, but a new problem arises which is the dierence in the measurement of the H0 value. This dierence occurs between measurements based on local observations using the distance-ladder method and global measurements using Cosmic Microwave Background (CMB) data. Various solutions have been proposed to overcome this problem, such as identi- fying and including systematic errors that have not been taken into account so far, independent measurements of the distance ladder and CMB, as well as new physics beyond the standard CDM cosmological model. Most of the new physics proposed require adding completely new independent parameters, or making parameters those are xed in the CDM model become independent parameters. Although many of these modications have succeeded in reducing the mismatch between local and global H0 measurements, this was often achieved due to the large error in the H0 values obtained. Therefore, this nal project will study the possibility to overcome this problem by modifying the CDM parameter from its standard value, without increasing the number of independent parameters, to produce a suitable H0 value between local and global measurements without increasing the uncertainty in the H0 value. Furthermore, it will be compared with the case if the independent parameter of CDM is added, by making one or two dierent values from the standard values (converted to independent parameters). Parameter modication in this nal project focuses on the equation of state parameters (w) and the eective number of neu- trino species (Neff ). The cosmological models reviewed were then compared with the CDM model using Bayesian factor calculation, to determine which model is the preferred by data. In this nal project, it was found that the values of w ????1;3 and Neff 3;95 were able to overcome the dierences in the measurement of H0 values locally and globally.